The Effects of A 7-Minute HIIT Workout on Stress and Burnout in Outpatient Physical Therapists - Salvo Charles; Kissling Kristin; Bearzi Andre; Bondarenko Victoria; Llanso Tate; Tolley Luke; Weinstock-Collins Matthew; Caputo Matthew (International Journal of Occupational and Environmental Medicine, 2024)
Physical therapists (PTs) experience stress and burnout due to high job and productivity demands. Exercise can assist in decreasing stress and burnout, but finding the time to exercise can be difficult. This study examined the effects of a 28-day, 7-minute, high intensity interval training (HIIT) workout on PT’s stress and burnout levels. In this quasi-experimental pretest-posttest design, the Perceived Stress Scale, Maslach Burnout Inventory, grip strength, Functional Reach Test, and VO2max measures were administered on day 1 and day 28. Between the data collection period, participants completed a daily, 7-minute HIIT workout. A series of paired sample t-tests were computed to compare the pre- and post-HIIT raw values. Significant improvements were found in all comparisons post-HIIT (p< .001). Therefore, it was concluded that 7-minutes of HIIT can assist PTs in reducing stress and burnout levels. Employers should consider implementing a workplace wellness program to benefit their employees.
Keywords: Stress